Metabolic labeling of cardiomyocyte‐derived small extracellular‐vesicle (sEV) miRNAs identifies miR‐208a in cardiac regulation of lung gene expression. Issue 10 (17th October 2022) - Han, Chaoshan; Yang, Junjie; Zhang, Eric; Jiang, Ying; Qiao, Aijun; Du, Yipeng; Zhang, Qinkun; An, Junqing; Sun, Jiacheng; Wang, Meimei; Nguyen, Thanh; Lal, Hind; et al.
Abstract: Toxoplasma gondii uracil phosphoribosyltransferase (UPRT) converts 4‐thiouracil (4TUc) into 4‐thiouridine (4TUd), which is incorporated into nascent RNAs and can be biotinylated, then labelled with streptavidin conjugates or isolated via streptavidin‐affinity methods. Here, we generated mice that expressed T. gondii UPRT only in cardiomyocytes ( CM UPRT mice) and tested our hypothesis that CM‐derived miRNAs ( CM miRs) are transferred into remote organs after myocardial infarction (MI) by small extracellular vesicles (sEV) that are released from the heart into the peripheral blood ( PB sEV). We found that 4TUd was incorporated with high specificity and sensitivity into RNAs isolated from the hearts and PB sEV of CM UPRT mice 6 h after 4TUc injection. In PB sEV, 4TUd was incorporated into CM‐specific/enriched miRs including miR‐208a, but not into miRs with other organ or tissue‐type specificities. 4TUd‐labelled miR208a was also present in lung tissues, especially lung endothelial cells (ECs), and CM‐derived miR‐208a ( CM miR‐208a) levels peaked 12 h after experimentally induced MI in PB sEV and 24 h after MI in the lung. Notably, miR‐208a is expressed from intron 29 of α myosin heavy chain (αMHC), but αMHC transcripts were nearly undetectable in the lung. When PB sEV from mice that underwent MI (MI‐ PB sEV) or sham surgery (Sham‐ PB sEV) were injected into intact mice, the expression of Tmbim6 and NLK, which are suppressed by miR‐208a and cooperatively regulate inflammation via the NF‐κB pathway, was lower in the lungs of MI‐ PB sEV–treated animals than the lungs of animals treated with Sham‐ PB sEV or saline. In MI mice, Tmbim6 and NLK were downregulated, whereas endothelial adhesion molecules and pro‐inflammatory cells were upregulated in the lung; these changes were significantly attenuated when the mice were treated with miR‐208a antagomirs prior to MI surgery. Thus, CM UPRT mice enables us to track PB sEV‐mediated transport of CM miRs and identify an miR‐208a‐mediated mechanism by which myocardial injury alters the expression of genes and inflammatory response in the lung.